Automobile electrical & electronic systems the Haynes manual for understanding and troubleshooting automobile electrical and electronic systems - Randall, Martynn (Haynes manual, 2006)
This is a guide to the essential theory and practice for all car electrical and electronics systems. It covers charging and starting systems, batteries, instrument displays, lighting and signalling systems and much more